Prediksi Umur Lelah Lower Suspension Arm Minibus yang Dikemudikan pada Permukaan Jalan Lurus dan Berbelok Berbasis Pendekatan Strain-Life - Zainal; Ajinar (Journal of Engineering and Science, 2022)
In the previous studies, prediction of fatigue life at the lower suspension arm is only done based on strain signals obtained on a straight road. Considering the main function of the lower suspension arm is to stabilize the vehicle when turning, the purpose of this study is to predict the fatigue life of the lower suspension arm when the vehicle goes straight and turns clockwise and counterclockwise. The three roads are passed by vehicles with a speed of 30 km/hour. Measurement of strain signals is done by attaching a strain gauge to the lower suspension arm on the left side of the vehicle. Based on the simulation results based on the strain-life approach the lowest fatigue life is given by turning clockwise direction with 2.56E+6 cycles so that it breaks using the Coffin-Manson model. This value is low than the age of fatigue life when the vehicle goes straight and turns counterclockwise, each with 5.85E+6 cycles so it breaks and 5.08E+7 cycles so it breaks. This value is also comparable to that produced by the Morrow and SWT models. When the vehicle turns right, the lower suspension arm on the left side receives a strain that is greater than when the vehicle turns left, which is 5%. Strain received by the lower suspension arm can shorten the fatigue life of the component. Turning roads shorten the fatigue life of lower suspension arm so that 44% compared to straight roads.